National Electronic Government Comparing governance structures in multi-layer administrations - Martin Eifert , Jan Ole PÃ¼schel (Routledge, 2004)
This book is based on research carried out within the framework of the MEDIA@Komm initiative of the German federal government (Ministry of Economics and Labour). The initiative aimed at promoting advanced egovernment solutions and is described in greater detail in the chapter on Germany. Apart from the funding of three promising pilot cities which had been at the heart of the project, the initiative also included accompanying research on all relevant aspects of advanced e-government. This research was conducted by a consortium of institutions, namely the Hans Bredow Institute for Media Research (Hamburg) in co-operation with the Centre for Research in Law and Innovation (CERI, Hamburg University), the German Institute for Urban Affairs (DIfU, Berlin), the German Standardisation Institute (DIN, Berlin) and TÃœV IT (Essen). One part of this research had been an international comparison of e-government developments conducted by the Hans Bredow Institute in cooperation with CERI and DIfU. The first-mentioned institutions had been in charge of an analysis of the institutional framework of cooperation and coordination, on which this book is based.